2003
DOI: 10.1076/apab.111.3.217.23459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of U-46619 on Pulmonary Hemodynamics Before and After Administration of BM-573, a Novel Thromboxane A2 Inhibitor

Abstract: We studied the effects on pulmonary hemodynamics of U-46619, a thromboxane A 2 (TXA 2 ) agonist, before and after administration of a novel TXA 2 receptor antagonist and synthase inhibitor (BM-573). Six anesthetized pigs (Ago group) received 6 consecutive injections of U-46619 at 30-min interval and were compared with six anesthetized pigs (Anta group) which received an increasing dosage regimen of BM-573 10 min before each U-46619 injection. Consecutive changes in pulmonary hemodynamics, including characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For the pulmonary circulation, our results evidenced significant correlation between both methods, as well as between E a ‫ء‬ (PV) and RT/T, despite dramatic changes in pulmonary vascular compliance. Our laboratory previously showed a concordant evolution between E max /E a and stroke work in pulmonary embolism or septic shock (6,13,15). This could be explained by higher basal pulmonary vascular compliance compared with the values obtained on the systemic circuit.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For the pulmonary circulation, our results evidenced significant correlation between both methods, as well as between E a ‫ء‬ (PV) and RT/T, despite dramatic changes in pulmonary vascular compliance. Our laboratory previously showed a concordant evolution between E max /E a and stroke work in pulmonary embolism or septic shock (6,13,15). This could be explained by higher basal pulmonary vascular compliance compared with the values obtained on the systemic circuit.…”
Section: Discussionmentioning
confidence: 93%
“…Our laboratory previously showed that, in heart failure due to pulmonary embolism and sepsis, the decreased value of E max /E a was related to an impaired use of energy by the failing heart (6,13,15). In combination with E max , E a (PV) appears to be a simple way to characterize ventriculo-arterial interaction (18,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal operating conditions, the right ventricle operates at a maximum efficiency and a submaximal stroke work ( /( > 1), while uncoupling occurs when / < 1 (Fourie et al, 1992, Lambermont et al, 2003a.…”
Section: Discussionmentioning
confidence: 99%
“…This novel TXA 2 receptor antagonist and synthase inhibitor has a powerful antiplatelet potency and was shown to relax the rat aorta artery precontracted with U-46619, a stable TXA 2 agonist [21][22][23]. In the pig, our team demonstrated that BM-573 revealed a protective effect against pulmonary hypertension induced by U-46619 [24]. Besides, we also reported the preventive effect of BM-573 in the early phase of endotoxin induced pulmonary hypertension [25], and during embolic induced pulmonary vasoconstriction [26].…”
Section: Introductionmentioning
confidence: 99%